Screening of tree cotton (Gossypium arboreum) germplasm to grey mildew caused by Ramularia areola - Mukewar, P M; Raj, Sheo; Singh, V V; Anap, G R (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during 1985-89 to evaluate 1 489 germplasm lines of tree cotton (Gossypium arboreum L.) for their reaction to grey mildew caused by Ramularia areola Atkinson. Under natural conditions of disease occurrence, 24 lines were found free of infection. These infection-free lines were tested further by artificial inoculation in screen-house and in field during 3 crop seasons of 1989-92, which revealed the presence of 7 immune and 17 highly resistant lines. The immune lines identified were 'Bangladesh', 'G 135-49' (G. arboreum L. race bengalense Silow), '30805', '30814', '30826', 30838' and '30856' (G. arboreum L. race cernuum Silow). AmongÂ  17 highly resistant lines belonging to G. arboreum race bengalense, 7 ('AC 631', 'AC 727 DH', 'AC 727 MH', 'Desi 1', 'G 112', 'H 574' and 'K 53-519') showed desired staple length and 8 (' AC 24', 'AC 631', 'AC 727 DH'. 'AC 727 MH', 'Desi 1', 'G 112', 'Gao-CB 3 NLL' and 'H 574') showed desired fibre fineness, which were comparable with those of variety 'AKH4'.